The Impacts of Fiscal Instruments and Socioeconomic Factors on Poverty - Annisa, Nur; Susilo (Journal of Development Economic and Social Studies, 2026)
Despite receiving the largest Special Autonomy Fund (SAF), Aceh maintains the region’s highest poverty rate in Sumatra. Furthermore, the decline in Social Assistance Spending (SAS) is in line with the decline in poverty. On the other hand, high GRDP per capita, education, and health, coupled with low poverty, are not uniform across districts/cities. Therefore, this study analyses the impact of government interventions and socio-economic factors on poverty across 23 Aceh districts/cities from 2017 to 2024 using panel data multiple linear regression. Results indicate that the SAF and GRDP per capita have no significant effect due to infrastructure-heavy allocations and regionally concentrated growth. Meanwhile, SAS shows a positive effect, indicating recipient dependency and non-pro-poor allocations. Conversely, Education and Health have a negative effect, confirming the role of human capital. It is concluded that fiscal intervention does not guarantee poverty reduction if the allocation is inefficient. Furthermore, high GRDP per capita will not reduce poverty if it remains concentrated in only a few regions. Policymakers must restructure the use of SAF before 2027 while improving SAS targeting and agricultural downstreaming.